Efektifitas mindfulness terhadap tingkat kecemasan siswa SMK dalam menghadapi ajaran baru - Indarna, Asep Aep; Derajat, Agus Miraj; Widyawati, Widyawati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2024)
Background: Students' anxiety in facing new school teachings needs to be considered. Many studies have been conducted and show that anxiety is one of the factors that threatens students' quality of life and achievement at school. Mindfulness training is able to develop students' availability of learning resources, strengthen their availability to feelings, and reduce the impact of stress that threatens students' quality of life. Mindfulness combined with the availability of learning resources and awareness of feelings can help reduce students' anxiety levels in facing new school teachings. Purpose: To determine the effectiveness of mindfulness on vocational school students' anxiety levels in facing new teachings. Method: Experimental research with a quasi-experimental approach. The research design uses a pretest and posttest design. The research was carried out at the Bhakti Kencana Cimahi Health Vocational School in October 2024. The population in this study was all 228 class X students. The intervention group consisted of 50 participants and the control group consisted of 50 participants using a stratified random sampling technique. The instruments used were questionnaire sheets and observation sheets. The statistical test uses the Wilcoxon Sign Rank Test with a significance value of α = 0.05. Results: Before giving the mindfulness intervention to 50 participants there was a moderate level of anxiety (68%), and after being given the intervention the level of anxiety became mild (60%). The Wilcoxon Sign Rank Test results show a value of ρ = 0.001 (ρ<α). Conclusion: Mindfulness is effective in reducing the anxiety level of vocational school students in facing new teachings.   Keywords: Anxiety;  Mindfulness; Students.   Pendahuluan: Kecemasan siswa dalam menghadapi ajaran baru sekolah perlu dipertimbangkan. Banyak penelitian yang telah dilakukan dan menunjukkan bahwa kecemasan adalah salah satu faktor yang mengancam kualitas hidup dan prestasi siswa di sekolah. Pelatihan mindfulness mampu mengembangkan ketersediaan sumber daya belajar siswa, memperkuat ketersediaan mereka pada perasaan, dan mengurangi dampak stres yang mengancam kualitas hidup siswa. Mindfulness digabung dengan ketersediaan sumber daya belajar dan ketersederahan pada perasaan yang dapat membantu mengurangi tingkat kecemasan siswa dalam menghadapi ajaran baru sekolah. Tujuan: Untuk mengetahui efektifitas  mindfulness terhadap tingkat kecemasan siswa SMK dalam menghadapi ajaran baru. Metode: Penelitian eksperimental  dengan pendekatan quasi eksperimen. Rancangan penelitian menggunakan pretest and posttest design. Penelitian dilaksanakan di SMK Kesehatan Bhakti Kencana Cimahi pada bulan Oktober 2024. Populasi dalam penelitian ini adalah seluruh siswa kelas X sebanyak 228 orang. Kelompok intervensi sebanyak 50 partisipan dan kelompok kontrol sebanyak 50 partisipan dengan teknik pengambilan sampel stratified random sampling. Instrumen yang digunakan adalah lembar kuesioner dan lembar observasi. Uji statistik menggunakan Uji Wilcoxon Sign Rank dengan nilai kemaknaan α = 0.05. Hasil: Sebelum pemberian intervensi  mindfulness kepada 50 partisipan terdapat tingkat kecemasan sedang (68%), dan setelah diberikan intervensi tingkat kecemasan menjadi ringan (60%). Hasil Uji Wilcoxon Sign Rank menunjukkan nilai ρ = 0.001 (ρ < α). Simpulan:  Mindfulness efektif dalam menurunkan tingkat kecemasan siswa SMK dalam menghadapi ajaran baru.   Kata Kunci: Kecemasan;  Mindfulness; Siswa.